Assortative Mating and Female Labor Supply - Bredemeier, Christian; Juessen, Falko (Journal of Labor Economics, 2013)
This paper investigates married women’s hours worked disaggregated by the husband’s wage decile. In the United States, this pattern has changed from downward sloping to hump shaped. We show that this development can be explained within a standard household model of labor supply when taking into account trends in assortative mating. A quantitative analysis of our model shows that female wage growth and decreasing fertility are primarily responsible for the overall increase in wives’ hours since the 1970s. The fact that the most pronounced increases are observed for wives married to high-wage men is a result of trends in assortative mating.